Wounds Care on Patients During The Covid-19 Pandemic Era - Zega, Petra Diansari; Bui, Thanh Loan; Sembiring, Adelina (Lembaga Publikasi Ilmiah Nusantara, 2023)
Introduction: Wound care is part of nursing management. During Covid-19, the practice of wound care decreased under normal conditions. Nursing management knowledge is needed on how to practice wound care during COVID-19 to provide a wound healing process. This systematic review aims to identify wound care nursing care management during COVID-19. Methods: Article searched from PubMed; ProQuest; and EBSCO; selected based on the following inclusion criteria: study focus on nurses practicing chronic wound care during Covid-19, focused nursing management, case studies, articles published in the 2019-2021 range, full text, articles in English. Results: In the final stage, 5 articles were found. The results of the study show that nursing care management uses telehealth and telemedicine services for wound care patients. Conclusion: The findings of this systematic review indicate that telehealth and telemedicine services can provide opportunities to improve wound care to patients.